(untitled) - Chamizo-Domínguez, Pedro J. (New York, 2008)
This book approaches the topic of false friends from a theoretical perspective, arguing that false friends carry out a positive role as a cognitive device, mainly in literature and jokes, and suggesting some pragmatic strategies in order to restore the original sense of a text/utterance when a given translator (or a foreign speaker) falls victim to false friends. This theoretical account is successively verified by appealing to texts from the fields of literature, science, philosophy, journalism, and everyday speech.
Keywords: Translating and interpreting,Biên dịch và phiên dịch